2006
DOI: 10.1093/hmg/ddl205
|View full text |Cite
|
Sign up to set email alerts
|

Usher syndrome: molecular links of pathogenesis, proteins and pathways

Abstract: Usher syndrome is the most common form of deaf-blindness. The syndrome is both clinically and genetically heterogeneous, and to date, eight causative genes have been identified. The proteins encoded by these genes are part of a dynamic protein complex that is present in hair cells of the inner ear and in photoreceptor cells of the retina. The localization of the Usher proteins and the phenotype in animal models indicate that the Usher protein complex is essential in the morphogenesis of the stereocilia bundle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
196
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(208 citation statements)
references
References 90 publications
9
196
0
Order By: Relevance
“…37 Like nucleoredoxin, the Usher protein complex is an effector of b-catenin, and also affects neuronal morphogenesis and structural plasticity. 38 Usher syndrome can cause central nervous system structural changes 39 and psychosis, 40 and there is one report of increased incidence of bipolar disorder among adults with prelingual-onset nonsyndromic deafness, 41 but it is not known if any of those patients carried the 'whirler' mutation. Finally, SORCS2 maps to a region on chromosome 4p that has been widely linked to bipolar disorder 42 (Supplementary References).…”
Section: Ae Baum Et Almentioning
confidence: 99%
“…37 Like nucleoredoxin, the Usher protein complex is an effector of b-catenin, and also affects neuronal morphogenesis and structural plasticity. 38 Usher syndrome can cause central nervous system structural changes 39 and psychosis, 40 and there is one report of increased incidence of bipolar disorder among adults with prelingual-onset nonsyndromic deafness, 41 but it is not known if any of those patients carried the 'whirler' mutation. Finally, SORCS2 maps to a region on chromosome 4p that has been widely linked to bipolar disorder 42 (Supplementary References).…”
Section: Ae Baum Et Almentioning
confidence: 99%
“…In the stereocilia myosin VIIa localizes to the actin bundles and forms the lateral and ankle links in between stereocilia along with its numerous binding partners e.g. vezatin and harmonin b and the cadherin/␣-catenin complex (49,50). It has been suggested that myosin VIIa is responsible for maintaining the tension by linking the stereocilial membrane to the actin core thus causing tension in membrane-bound elements such as transducer channels, the tip link and the lateral links.…”
mentioning
confidence: 99%
“…Increasing evidence suggests that products of Usher type I and II genes form large networks of interacting proteins, and that F-actin plays a major role in organizing these networks (reviewed in Refs. 2,9). The core of these networks is the Usher type IC gene product, Harmonin, which interacts directly with F-actin in vitro and stabilizes F-actin when it is expressed heterologously in HeLa cells (10).…”
mentioning
confidence: 99%
“…Harmonins retain multiple PDZ domains dedicated to interacting with products of Usher type I and type II genes (reviewed in Refs. 2,9) and also serve as PDZ domainbased scaffolds to anchor Usher proteins to F-actin. A link between Usher gene products and actin-based organelles also has been established in vivo.…”
mentioning
confidence: 99%